Discursos da aporofobia na mídia digital brasileira: hostilidade à população em situação de rua - Nascimento, Elislane de Goes (2025)
This research aims to investigate the discursive practices related to the homeless population (PSR) in Brazilian digital media. The corpus consists specifically of news, posts, and comments on Instagram and on journalistic or institutional websites, in which aporophobia manifests itself and in which political and religious antagonisms, resistance, and the beliefs of the subjects emerge. The main objective of this investigation is to understand how discourses of hostility towards the homeless people are constituted in the Brazilian media. To achieve this, we are guided by the conceptualization of aporophobia developed by the Spanish philosopher Adela Cortina, as well as discussions that are transversally linked to the theme in the field of a philosophy of migrations and the history of foreignness (Salomão, 2021; Farias, 2018; Derrida, 2003). Furthermore, within the theoretical-methodological framework of French Discourse Analysis (DFA), especially in Foucauldian Discursive Studies (FDS) (Curcino, 2024, 2020; Foucault, 2022, 2014, 2013, 2006, 2005, 1999; Ribeiro, 2022, 2015; Courtine, 2022, 2013; Piovezani, 2020; Sargentini, 2014, 2011; Fernandes, 2014, 2012; Gregolin, 2006), which underpin the research, we take concepts such as discursive formation, statement, archive and subject. We are guided by the following questions: how are discourses of aporophobia against/with homeless people constituted? What discursive formations are they affiliated with and what are the production conditions aporophobic discourses about this group of subjects?? We start from the hypothesis that discourses about the homeless, disguised as opinions, are linked to hostility, which results in the dehumanization of these impoverished individuals. They supposedly represent a danger from the point of view of a policy based on the criminalization of poverty (Salomão, 2021). On the other hand, Christian ideology and messianic discourse would be at the heart of the welcome and, thus, of aporophilia, but also in the individual blaming of poverty, as the meritocratic neoliberal discourse would have us believe. We confirm the hypothesis that discourses about the homeless people carry marks of hostility, which we found to be impregnated with stereotypes and social prejudices, resulting in their criminalization. It was also noted that the appearance of discourses linked to religiosity in statements about the homeless population is linked to the figure of Júlio Lancellotti and that there is an existing contradiction, in a political context, between the supposed image of Christian subjects and the misalignment between this image and the attitudes materialized in the discourse that many of these subjects support.